PENINGKATAN PENDAPATAN PETANI LADA MELALUI PERBAIKAN SISTEM USAHATANI - SAHARA, DEWI; -, YUSUF; -, SUHARDI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005, 2012)
The research on increasing farmer’s income thorough repairing pepper farming sistem had done on November to December 2003 in Mowila and Lakomea villages, Landono sub district, Kendari regency, Southeast Sulawesi. The research aimed to know farmer’s income degree who repaired their farming sistem with integrated farming sistem compared farmer’s income who used monoculture sistem so that to obtain description of different degree of income. The research was survey method and direct interviewed to 14 farmers who integrated pepper with goat livestock and 16 farmers who had monoculture sistem. The result showed that pepper productivity on integrated farming sistem reached 622,30 kg/ha while monoculture reached 242,85 kg/ha or 156,63 % in different. Difference of production caused difference of income Rp 5.536.919,23 each year or 341,85 % in different. Income contribution of goat livestock on pepper farming sistem was 27,18 % of totally farmer’s income. Besides as added value, goat livestock can also as a source of organic matter and could 50, 54 % production cost of total production economically. Therefore, to sustainability of pepper farming sistem and to emphasize production cost, raise goat livestock insentivelly near pepper area can be done.
Keywords: Iincome, Farming Sistem, Pepper, Goat Livestock